Nanomaterials from the Bench to Industry: An Experience in an Emerging Country - Britto, Fiona Macarena; Penelas, María Jazmín; Lombardo, Maria Veronica; Alderete, Mara; Soler Illia, Galo Juan de Avila Arturo (CRC Press - Taylor & Francis Group, 2023)
Fil: Britto, Fiona Macarena. Universidad Nacional de San Martin. Instituto de Nanosistemas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina